Study of Silicon Nitride Inner Spacer Formation in Process of Gate-all-around Nano-Transistors - Junjie Li; Yongliang Li; Na Zhou; Wenjuan Xiong; Guilei Wang; Qingzhu Zhang; Anyan Du; Jianfeng Gao; Zhenzhen Kong; Hongxiao Lin; Jinjuan Xiang; Chen Li; et al. (Nanomaterials, 2020)
Stacked SiGe/Si structures are widely used as the units for gate-all-around nanowire transistors (GAA NWTs) which are a promising candidate beyond fin field effective transistors (FinFETs) technologies in near future. These structures deal with a several challenges brought by the shrinking of device dimensions. The preparation of inner spacers is one of the most critical processes for GAA nano-scale transistors. This study focuses on two key processes: inner spacer film conformal deposition and accurate etching. The results show that low pressure chemical vapor deposition (LPCVD) silicon nitride has a good film filling effect; a precise and controllable silicon nitride inner spacer structure is prepared by using an inductively coupled plasma (ICP) tool and a new gas mixtures of CH2F2/CH4/O2/Ar. Silicon nitride inner spacer etch has a high etch selectivity ratio, exceeding 100:1 to Si and more than 30:1 to SiO2. High anisotropy with an excellent vertical/lateral etch ratio exceeding 80:1 is successfully demonstrated. It also provides a solution to the key process challenges of nano-transistors beyond 5 nm node.